Space occupation near the basket shapes collective behaviours in youth basketball - Esteves, P. T.; Silva, P.; Vilar, L.; Travassos, B.; Duarte, R.; Arede, J.; Sampaio, J. (Journal of Sports Sciences, 2016)
This study aimed to analyse how youth basketball players explored numerical overloads during shot attempts by measuring their space occupation across specific court areas. Four process-tracing variables measured how the number of attackers (NA), number of defenders (ND), interpersonal distance between attacker and the closest defender (ID) and distance between attacker and the basket (DBkt) impacted on the performance outcome (converted shot; missed shot; ball possession lost). Ten competitive games involving 13 U14 teams were video recorded and players` displacements were digitised. The associations between performance outcomes and the process-tracing measures were assessed using standardised mean differences and a cross-correlation function. A multinomial logistic regression was used to calculate the odds ratio (OR) for each of the three possible outcomes. Results revealed that when shot attempts occurred at larger ID and at smaller DBkt, the possibilities to obtain a converted shot increased. The numerical overload of defenders near the scoring target was predominantly associated with offensive success. Also, the possibility of attackers to lead the spatial relation of movements with the defenders, near the scoring target, appeared as a prominent strategy to succeed. In sum, basketball teams that exhibit potential to adapt their collective behaviours to local changes in the environment might be closer to achieving successful outcomes.